Infrastructure sector in India in the post liberalisation era - Rao, K. Viyanna; Rao, Chandra Sekhara (1999)
Adequate quantity, quality and reliability of infrastructure facilities are sine quanon for the development of a nation. The availability of these facilities is all, the more significant and relevant in case of a developing economy like India; which is engulfed with teeming millions of population. Because of its pervasive impact on economic development and human welfare an attempt has been made in this paper to review the performance of infrastructure of sector in India and to explore the ways in which India can improve the quantity and quality of physical infrastructure to realise the full impact of economic reforms initiated in recent years. In this context, the present paper focuses its attention on the present position of infrastructure sector in India, reforms initiated by the government during the past few years; the impact of these reforms on the working of different infrastructure sectors; gaps existing in the infrastructure; and the future policy direction. The paper concludes with a suggestion to the government of India for adopting a more realistic approach in tackling the problems of infrastructure development. - Reproduced
Keywords: Liberalization - India; Infrastructure development - India; Infrastructure development